Application of Gamification with "SIKMA" to Increase Motivation and Learning Independence Attitudes - Ilmadi; Aldi Florensius Gea; Joshua Damas Sadewo; Uswantun Hasanah; Enggar Prasetyawan; Totok Victor Didik Saputro; Syifa Rahmawati; Maulida Nurazizah; Anisa Nurfebrianti; Teresia Wini; Santi Suprapti (Asian Journal of Community Services, 2023)
This Community Service Activity (PKM) aims to increase the motivation and independence of learning for students in Porisgaga Housing, Ambon Block, Tangerang City, so that the use of Smartphones can be used as a tool to support the learning process outside of class hours (outside of school). Most students use smartphones outside of school to play games, so their time is spent on the game, so the function of the smartphone, which was originally to support the learning process, turned into access to playing online games. One effective way to solve this problem is the application of gamification with the concept of "SikMa". SikMa is a gamification that is conceptualized based on the fun of learning mathematics, after applying gamification with the concept of sikma, more than 80% of students stated that learning using the SikMa concept is more fun, and their learning independence is increased. This can be seen from their atusias working on the exercises given through gamification, from the results of the survey after being carried out PKM it was found that more than 60% of students are motivated in learning and more than 50% of them have a good attitude of learning independence.